Role of ion beam excitations on quasi one-dimensional magnetic system of Mn-doped LiCuVO4 - Kumar A.; Dwivedi G.D.; Kumar S.; Shahi P.; Shukla K.K.; Ghosh A.K.; Asokan K.; Kanjilal D.; Singh R.K.; Nigam A.K.; Chatterjee S. (My University, 2025)
Abstract Induction of short range ferromagnetic ordering has been observed in the quasi one dimensional antiferromagnetic LiCuVO4 system with doping of Mn in the octahedral (Cu) site. Though, magnetic ordering is not stable enough as further increase of Mn-concentration, magnetic ordering gets deteriorated. This might be the case that Mn2+ ions, with strong magnetic moment as compared to Cu2+ ions, enhance the ferromagnetic coupling between the nearest neighbor atoms of quasi-one-dimensional magnetic LiCuVO4 system. Ferromagnetic ordering in LiCu0.95Mn0.05VO4 system also degraded after high energy ion beam excitation which creates defects and may disturb the short range ferromagnetic ordering in its near locality but it does not have much effect on the long range antiferromagnetic ordering. Irradiation causes no change in Raman modes of LiCu0.95Mn0.05VO4 system, while it produces some new vibrational modes in intermediate and high frequency region of LiCu0.9Mn0.1VO4 system. Above results have been understood based on competitions between ferromagnetic nearest neighbor (NN) coupling and antiferromagnetic next nearest neighbor (NNN) coupling in CuO2 chain. © 2015 Elsevier B.V.